A new method measurement for finger range of motion using a smartphone. Issue 4 (3rd July 2020) - Miyake, Keisuke; Mori, Hideki; Matsuma, Sayoko; Kimura, Chizu; Izumoto, Mamiko; Nakaoka, Hiroki; Sayama, Koji
Abstract: The protractor-based goniometer is the standard instrument used to measure finger range of motion (ROM). However, the method is often complicated to apply and places a burden on the investigator. Here, we developed a new method for finger ROM measurement using a smartphone. This study was performed to determine the reliability and convenience of this new method. The ROM in 1007 finger joints was measured by both the standard and new method and the data were analyzed using the intraclass correlation coefficient (ICC). The smartphone ICC score was high (0.927), and the average measurement time per joint was 49% lower with the smartphone compared to the goniometer. The results indicated that the smartphone-based measurement method had the same reliability as the conventional goniometer, in addition to an excellent measurement time.